Agricultural development In India - Bisht, Devendra Singh (New Delhi, 1989)
Agricultural Development in India' is a pioneering work having its principal focus on the processes of agrarian inno vations, new technology and its policy imperatives. The subject matter covers the modes and processes of 'diffusion' of innovations in common mass of agrarian entrepreneurs. The issues of social change and economic development, by growth of agricultural inputs and their application, have been covered by the author in a lucid style. Mass communi cation media, vehicles of information, channels of spreading knowledge and infra-structure strengthening the process of diffusion of innovations have been covered. It gives a vivid account of agricultural growth in India and agri cultural development in its various regions.
Keywords: Land reformsIndia